PENGARUH IMPLEMENTASI KESELAMATAN KECELAKAAN KERJA (K3) DAN DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN DI HOTEL TIRTA SANITA RESORT - Selviteria Alnaseri; Sari Laelatul Qodriah; Harry Safari Margapradja (P3M Politeknik Negeri Ambon, 2025)
This research aims to analyze the impact of the implementation of Occupational Health and Safety (OHS) and organizational support on employee performance at Hotel Tirta Sanita Resort. The issue raised focuses on the importance of a safe work environment and organizational support in improving employee performance, especially in the hospitality service industry. This study uses a quantitative approach with a purposive sampling technique, involving 60 respondents who have worked for at least one year and are directly involved in hotel operations. Data were collected through questionnaires and analyzed using validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, and t-tests. The research results indicate that the implementation of OHS has a positive and significant effect on employee performance with a significance value of 0.003. Organizational support also has a significant effect with a significance value of 0.000 and has a stronger influence compared to OHS. Simultaneously, both variables have been proven to significantly affect performance improvement. These findings point out the value of synergy between physical protection through OHS and psychological support through the organization in creating a productive work environment. This research recommends that hotel management consistently enhance the implementation of OHS programs and strengthen the organizational support culture to encourage optimal employee performance. Keywords: Occupational Safety and Health (OSH), Organizational Support, Employee Performance, Hospitality Industry, HR Management